RELASI AGAMA DAN NEGARA DILIHAT DARI KEBERADAAN LEMBAGA PERBANKAN SYARIAH - Orien Effendi (Universitas Islam Negeri Mataram, 2021)
between religion and the state towards the existence of Islamic banking, although at first glance this paper seems to touch on the realm of state administration, in essence, this paper focuses on discussing the scope of muamalah in the context of Islamic banking. Basically, the state is present in the interests of religion, including the realm of sharia-based economics, through this sharia-based banking institution, the sharia economy can develop and become a new alternative for the majority of Indonesian who are Muslim, through Islamic banking products that apply the concept with the provisions of Islamic law. What is meant by the presence of the state in the context of sharia banking is of course in the realm of providing clear regulations or a legal system in the form of laws and regulations on Islamic banking activities, both from the provision of banking legal legality rules in the context of operations and related to all forms of Islamic banking products. which is applied according to the concept of sharia. Thus the presence of the state can guarantee legal certainty in the context of a sharia-based economy. This paper uses an analytical study method with a literature research model from primary and secondary data sources with a juridical normative approach.